Architecture of the Yeast RNA Polymerase II Open Complex and Regulation of Activity by TFIIF - Fishburn, James (American Society for Microbiology, 2012)
To investigate the function and architecture of the open complex state of RNA polymerase II (Pol II), Saccharomyces cerevisiae minimal open complexes were assembled by using a series of heteroduplex HIS4 promoters, TATA binding protein (TBP), TFIIB, and Pol II. The yeast system demonstrates great flexibility in the position of active open complexes, spanning 30 to 80 bp downstream from TATA, consistent with the transcription start site scanning behavior of yeast Pol II. TFIIF unexpectedly modulates the activity of the open complexes, either repressing or stimulating initiation. The response to TFIIF was dependent on the sequence of the template strand within the single-stranded bubble. Mutations in the TFIIB reader and linker region, which were inactive on duplex DNA, were suppressed by the heteroduplex templates, showing that a major function of the TFIIB reader and linker is in the initiation or stabilization of single-stranded DNA. Probing of the architecture of the minimal open complexes with TFIIB-FeBABE [TFIIB–p-bromoacetamidobenzyl–EDTA-iron(III)] derivatives showed that the TFIIB core domain is surprisingly positioned away from Pol II, and the addition of TFIIF repositions the TFIIB core domain to the Pol II wall domain. Together, our results show an unexpected architecture of minimal open complexes and the regulation of activity by TFIIF and the TFIIB core domain.